2010
DOI: 10.1002/cphc.201000208
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Gold and Platinum Nanowires on Graphite Edges

Abstract: The stability of coinage and noble metal nanowires supported on graphite steps is examined by density functional theory. In particular, we study the stability of supported gold and platinum wires and compare their chemical properties with those of surfaces and bare wires. A substantially stronger bond with graphite was found for platinum wires due to unfilled antibonding states, which are occupied in the case of gold. This difference has direct consequences for the adsorption of hydrogen. This reaction can occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a previous work we have investigated Pt and Au wires at the zigzag edge of graphite sheets. 32 In this work we extend our study to six metals (Ni, Pd, Pt, Cu, Ag, and Au) forming wires at the two stable graphite step edges: zigzag and armchair steps (see Figures 1 and 2). The catalytic properties for hydrogen oxidation are also investigated.…”
Section: ■ Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In a previous work we have investigated Pt and Au wires at the zigzag edge of graphite sheets. 32 In this work we extend our study to six metals (Ni, Pd, Pt, Cu, Ag, and Au) forming wires at the two stable graphite step edges: zigzag and armchair steps (see Figures 1 and 2). The catalytic properties for hydrogen oxidation are also investigated.…”
Section: ■ Introductionmentioning
confidence: 67%
“…We leave the cases of oxygen structures for a future study. In a previous work we have investigated Pt and Au wires at the zigzag edge of graphite sheets . In this work we extend our study to six metals (Ni, Pd, Pt, Cu, Ag, and Au) forming wires at the two stable graphite step edges: zigzag and armchair steps (see Figures and ).…”
Section: Introductionmentioning
confidence: 72%
“…However, it is known that isolated wires are impractical as electrocatalysts. Therefore, we focus in more realistic systems, where these nanowires are supported on inert substrates to examine their stability and the influence of their chemical properties on the electrocatalytic activity (for details, see [32]). Specifically, we considered Pt and Au monoatomic wires attached to monoatomic steps on the basal planes of graphite, the so-called graphite-supported wires (GSW).…”
Section: Intrinsic Chemical Nature and Geometrical Effect: Nobelmentioning
confidence: 99%
“…Considering the sp 2 hybridization of the carbon orbitals and the distance between two unsaturated carbon atoms (2.46Å), which fits quite well the bond distances of the bare wires (≈2.50Å), the zigzag arrangement was taken as the initial configuration. The system is shown in Figure 9-more detailed information can be found in [32].…”
Section: Intrinsic Chemical Nature and Geometrical Effect: Nobelmentioning
confidence: 99%
“…In previous works, we have performed ab initio investigations of both freestanding metal NW 23 and supported on step-edges. 24,25 More recently, we have found that in O 2 /H 2 atmosphere, the graphene edges are mainly oxidized. 26 On the armchair edges, the terminal carbons are carboxyl groups, but on the zigzag edges, we have found stable ketones and aldehyde groups.…”
Section: Introductionmentioning
confidence: 99%